Pengelolaan Zakat Dan Pengembangan Kegiatan Dakwah (Studi Badan Amil Zakat Nasional Provinsi Bengkulu) - Hariya Toni; Ahmad Zuhdi; Rafdeadi Rafdeadi (Jurnal Dakwah dan Komunikasi, 2022)
The religious program (Dakwah) is one of the main work programs at the National Amil Zakat Agency from the center to the regions. Although overall, BAZNAS activities are da'wah activities because the National Amil Zakat Agency is given the responsibility to manage the social piety of the people. The achievement of the goals of BAZNAS is strongly influenced by the ability to manage zakat funds and program implementation as well as the approach taken to mustahik and stakeholders. This research is a type of qualitative research with a descriptive approach to examine the management of zakat in the religious sector (da'wah) and examines the approach used by the Bengkulu Province National Amil Zakat Agency in the religious sector (da'wah) as an effort to achieve goals. The implementation of the distribution of zakat in the Bengkulu taqwa program is for TPA/MDA teachers and Islamic boarding schools 2%, assistance for TPA/MDA teachers and Islamic boarding schools 2%, assistance for houses of worship 2%, assistance for contract preachers is not up to 1%, assistance for muballigh/ muballighah 4%, operational assistance for TPA/MDA/foundations 25%, assistance for mosque and mushalla administrators 5%, assistance for religious activities 3% and assistance for compensation for teachers of the Koran 57%.